2014
DOI: 10.1016/j.otsr.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and MRI results in 67 patients operated for gluteus medius and minimus tendon tears with a median follow-up of 4.6 years

Abstract: Level IV-retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 23 publications
3
80
1
3
Order By: Relevance
“…Nonetheless, while rotator cuff pathology of the shoulder may interfere with daily activities, atrophy of the gluteus muscles contributes to gait disturbance and increases the risk of fall-related fractures [24][25][26][27][28][29]. While current treatment is primarily directed toward pain reduction, some surgeons have started to treat gluteus tendon tears aggressively with repair [30][31][32][33][34] with recent literature showing successful outcomes of repair [35].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, while rotator cuff pathology of the shoulder may interfere with daily activities, atrophy of the gluteus muscles contributes to gait disturbance and increases the risk of fall-related fractures [24][25][26][27][28][29]. While current treatment is primarily directed toward pain reduction, some surgeons have started to treat gluteus tendon tears aggressively with repair [30][31][32][33][34] with recent literature showing successful outcomes of repair [35].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The high rate of re-tears is likely related to the limited healing potential of tendinous tissue, which is poorly vascular and heals by formation of fibrocartilaginous scar tissue rather than histologically normal tendon. 10 Unlike a dermal graft, which provides immediate strength to repair, the bioinductive implant is intended to provide long-term improvement and reduced re-tear rates through amplification of the host healing response and induction of healthy tendon tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of full‐thickness tearing of either the GMIN or AB GMED tendon, diagnostic specificity will be reduced by communication between the sub‐GMIN or ‐GMED bursae and the more superficially located greater trochanteric bursa. Nonetheless, based on the likelihood that an advanced GMIN tendon disorder contributes to GTPS in the setting of an AB GMED tear, the GMIN is often repaired along with the AB GMED tendon in patients with severe or refractory pain or functional limitations …”
Section: Sonopathology Of the Gluteus Minimus Tendonmentioning
confidence: 99%
“…Gluteus minimus tendon disorders most commonly occur in conjunction with AB GMED tendon abnormalities but can also occur in isolation. 15,19,22 Pathology of the GMIN tendon may not always produce symptoms, as evidenced by the presence of abnormal findings on the asymptomatic contralateral side during the US evaluation. Similarly, several authors have reported magnetic resonance imaging abnormalities of the lateral hip in patients without trochanteric pain.…”
Section: Sonopathology Of the Gluteus Minimus Tendonmentioning
confidence: 99%
See 1 more Smart Citation